2012
DOI: 10.1542/peds.2011-1768
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Intravenous Palivizumab for Treatment of Persistent RSV Infection in Children With Leukemia

Abstract: Palivizumab is a humanized monoclonal antibody used to decrease the threat of respiratory syncytial virus (RSV) infection among children at high risk. There are no standard guidelines due to conflicting data on palivizumab's use in the treatment of RSV lower respiratory tract infections. Intravenous (IV) palivizumab was shown to be well tolerated and associated with decreased mortality in high-risk children who have RSV disease. However, it did not prevent lower respiratory tract infections and did not affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Six patients across the hospitals were given palivizumab to treat acute severe RSV infection. There is limited evidence to support use of palivizumab as treatment for RSV infection . There are case reports and case series that suggest intravenous palivizumab may be a treatment option for persistent RSV infection among immunocompromised patients …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six patients across the hospitals were given palivizumab to treat acute severe RSV infection. There is limited evidence to support use of palivizumab as treatment for RSV infection . There are case reports and case series that suggest intravenous palivizumab may be a treatment option for persistent RSV infection among immunocompromised patients …”
Section: Discussionmentioning
confidence: 99%
“…There is limited evidence to support use of palivizumab as treatment for RSV infection. 5,6 There are case reports and case series that suggest intravenous palivizumab may be a treatment option for persistent RSV infection among immunocompromised patients. 6 In 2015, fewer children (36%) received the full course of palivizumab, compared to 2014 (74%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Half the patients with SCID show a lymphocyte phenotype T−B+NK−, which is associated with defects in gamma-common chain or JAK3. [10][11][12][13] Oral RBV is equally efficacious as aerosolized RBV in the treatment of RSV infection in immunocompromised hosts. 5,6 The most common cause of acute bronchiolitis in infants, RSV, can be fatal in infants with SCID, as lymphopenia has been related to adverse outcome in viral infections in immunocompromised host.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled studies have shown that combined therapy with ribavirin and polyclonal or monoclonal antibodies is associated with decreased mortality, and a lower effect when monoclonal antibodies are administered alone . A report of two children with leukemia suggested that intravenous (IV) palivizumab, a monoclonal antibody against the RSV‐F protein, may be a treatment option for persistent RSV infection . The impact of IV palivizumab on respiratory or systemic viral loads and clinical outcomes in immunocompromised children has not been defined.…”
Section: Introductionmentioning
confidence: 99%